Louis T. Michener papers - Michener, Louis T. (Louis Theodore), 1848-1928.
Correspondence, memoranda, reports, newspaper clippings, printed matter, and autograph album relating chiefly to Indiana state politics, the Republican Party, and Michener's role in Benjamin Harrison's senate campaign of 1886 and presidential campaigns of 1888 and 1892. Correspondents include Albert Jeremiah Beveridge, Chauncey M. Depew, Frederick Douglass, Stephen B. Elkins, Joseph Benson Foraker, Walter Quintin Gresham, Mark Alonzo Hanna, Benjamin Harrison, Eugene Gano Hay, William McKinley, Joseph Homan Manley, John W. Noble, Henry C. Payne, Thomas Collier Platt, Albert G. Porter, Robert Stoddart Robertson, Theodore Roosevelt, Jeremiah McLain Rusk, John Sherman, William H. Taft, Lew Wallace, and John Wanamaker.
Lawyer, politician, and public official from Indiana.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Beveridge, Albert Jeremiah, -- 1862-1927 -- Correspondence; Depew, Chauncey M. -- 1834-1928 -- Correspondence; Douglass, Frederick, -- 1818-1895 -- Correspondence; Elkins, Stephen B. -- 1841-1911 -- Correspondence; Foraker, Joseph Benson, -- 1846-1917 -- Correspondence; Gresham, Walter Quintin, -- 1832-1895 -- Correspondence; Hanna, Marcus Alonzo, -- 1837-1904 -- Correspondence; Harrison, Benjamin, -- 1833-1901.; Harrison, Benjamin, -- 1833-1901 -- Correspondence; Hay, Eugene Gano, -- 1853-1933 -- Correspondence; Manley, Joseph Homan, -- 1842-1905 -- Correspondence; McKinley, William, -- 1843-1901 -- Correspondence; Noble, John W. -- 1831-1912 -- Correspondence; Payne, Henry C. -- 1843-1904 -- Correspondence; Platt, Thomas Collier, -- 1833-1910 -- Correspondence; Porter, Albert G. -- 1824-1897 -- Correspondence; Robertson, Robert Stoddart, -- 1839-1936 -- Correspondence; Roosevelt, Theodore, -- 1858-1919 -- Correspondence; Rusk, Jeremiah McLain, -- 1830-1893 -- Correspondence; Sherman, John, -- 1823-1900 -- Correspondence; Taft, William H. -- 1857-1930 -- Correspondence; Wallace, Lew, -- 1827-1905 -- Correspondence; Wanamaker, John, -- 1838-1922 -- Correspondence; United States. -- Congress. -- Senate -- Elections, 1886.; Republican Party (U.S. : 1854- ); Presidents -- United States -- Election -- 1888.; Presidents -- United States -- Election -- 1892.; Indiana -- Politics and government; United States -- Politics and government -- 1865-1933.; Lawyers; Politicians; Public officials -- Indiana